Using sigma-delta quantizer Based PI for inductive power transfer systems - Dhafer J. Almakhles; Akshya Swain; Hou Yuefeng (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this paper, a Sigma-Delta Quantizer (∑∆-Q) based Proportional and Integral control is proposed for a wireless power transfer control system, namely inductive power transfer system. The proposed control topology employs ∑∆-Qs to convert the conventional signals (analog/digital signals) into bitsreatm signals (1-bit per sample time). Considering the oversampling feature of ∑∆-Q, field programmable gate array is utilized in the implementation of the control system. To evaluate the effectiveness of the presented control topology, it is compared with an inductive power transfer control system using the conventional proportional and integral controller. For the sake of simplicity, the comparison is carried out using hardware in Loop. Both control systems exhibit almost identical responses. However, the bitstream feature of the proposed PI controller significantly helps in reducing the hardware resources (logic elements) in field programmable gate array. In addition, less wire routing and computational complexity is achieved due to absence of multipliers.